EVALUASI STRATEGI PENINGKATAN DANA MURAH DAN DIGITAL BANKING DI CIMB NIAGA - Ananda, Denta Felli (E-Jurnal Manajemen Trisakti School of Management (TSM), 2022)
Banking intermediation role an institution that gathers fund and distributes it to the are being challenged by the development of digital information technology that impact the entire industry. Bank’s ability to increase the low cost fund through digital banking platform will determine how the bank obtain a competitive advantage. This study aims to evaluate if the competitive strategies applied to increase low cost fund performance and the utilization of digital banking in PT Bank CIMB Niaga,Tbk has align with the corporate strategy. This framework is evaluating the strategy through qualitative research based on Rumelt’s framework, which consists of four stages, namely consistency, advantage, consonance, and feasible; using performance analysis, value chain, VRIO framework, and the concept of market orientation. The results of the study is that the strategy to increase low cost funds have been applied consistently, consonance, advance and feasibly to the corporate strategy. While the strategy to increase digital banking utilization that adopted has been conduct consistently, superior and fit, but not fully meet the feasibility. The recommendations are to affiliate low cost fund portfolio management as one of KPI main item for all employees, do the refinement of four leading digital platform that are currently running and to develop products that are interrelated between low cost funds and lending product throughout all directorate.